2020
DOI: 10.1039/d0sm01425g
|View full text |Cite
|
Sign up to set email alerts
|

Variable pitch hydrodynamic electro-optic gratings utilising bent liquid crystal dimers

Abstract: Electrohydrodynamic Instabilities in nematic liquid crystals cause uniform and continuously variable pitch diffraction gratings. Liquid crystal dimers allow greater range of elastic constants, allowing wider angle diffraction to be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 110 publications
(232 reference statements)
0
3
0
Order By: Relevance
“…Here, the maximum value η m ̸ = 0 of 33.9% occurs for the m = ±1 diffractive orders when ϕ max = 3.68. The most studied hydrodynamic NLC DOEs are created by electro-convection [24,[27][28][29][30][31][32]. These are instabilities caused by ion movement through the material induced by external electric fields [18,19,[33][34][35].…”
Section: Instabilities In Nlcs As Diffraction Gratingsmentioning
confidence: 99%
“…Here, the maximum value η m ̸ = 0 of 33.9% occurs for the m = ±1 diffractive orders when ϕ max = 3.68. The most studied hydrodynamic NLC DOEs are created by electro-convection [24,[27][28][29][30][31][32]. These are instabilities caused by ion movement through the material induced by external electric fields [18,19,[33][34][35].…”
Section: Instabilities In Nlcs As Diffraction Gratingsmentioning
confidence: 99%
“…One such is the Normal Roll (NR) texture caused by the director undulating to form an approximately 1D diffraction grating with Λ grat of order d [15,174]. Depending on the frequency, the value Λ grat can typically vary by a factor of two continuously [171,172,[175][176][177]. This typically allows wide-angle lowefficiency steering as the theoretical maximum η m=1 is around 40% without blazing, and significant optical losses occur within the devices.…”
Section: Flow-induced Patternsmentioning
confidence: 99%
“…Using EC, with a proper combination of the amplitude and frequency of the applied ac voltage, the direction of the wave vector and to some extent also its magnitude can be adjusted. It has been shown that by adding SBCN1 to the ionic-saltdoped, commercial nematic mixture MLC 2081, the range in which the wave number can be tuned by the frequency of the applied voltage could be substantially extended, both towards lower and higher q values [121]. This improvement has been attributed to the change of the elastic moduli (especially to the reduction of K3) occurring as a consequence of doping with the soft-core BCN.…”
Section: Periodic Patterns As Gratings For Optical Devicesmentioning
confidence: 99%